A rare late progression form of Sly syndrome mucopolysaccharidosis - Nathalie Guffon; Roseline Froissart; Alain Fouilhoux (JIMD Reports, 2019)
Abstract Mucopolysaccharidoses VII, or Sly syndrome, is linked to mutations in the beta‐glucuronidase encoding gene. Sly syndrome is a rare condition and presentation is highly variable, ranging from a prenatal form with severe, lethal fetal hydrops to more benign adolescent or adult forms with simple thoracic kyphosis. Molecular diagnosis of this adult male patient identified two missense mutations in the GUSB gene that led to a deficiency in beta‐glucuronidase catalytic activity and the resulting accumulation of chondroitin sulfate glycosaminoglycans. During childhood, bilateral inguinal hernia was repaired at 1 year of age and gait abnormalities were noted, leading to a bilateral femoral varization osteotomy due to a bilateral coxa valga with hip subluxation at the age of 7.5. The patient suffered regular upper respiratory infections and required numerous orthopedic surgeries. Despite learning difficulties with visual and hearing deficits, the patient worked full‐time and undertook regular leisure activities. At 33 years of age, the patient's health deteriorated; a hip replacement and glaucoma leading to reductions in his visual field limited his capacity to travel independently. The patient was hospitalized at 51. Although he remained self‐sufficient for taking meals, he needed help with many daily activities. Following a period marked by major asthenia with a general loss of autonomy, the patient died at 52 years of age. With the advent of new enzyme replacement therapies, this medical history of this rare untreated attenuated patient may provide benchmarks to judge the efficacy of treatment in future patients.